UKURAN PERUSAHAAN DAN KEPEMILIKAN PUBLIK SEBAGAI DETERMINAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN TAHUN 2022-2024 - Nurul Fahmi Sultan (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study aims to examine the effect of profitability, company size and public ownership on the sustainability report disclosure. This study uses quantitative research and uses secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). The data obtained were processed using SPSS analysis tool. The population used in this research is companies listed on the IDX in 2022-2024. The sampling method used in this study is purposive sampling method. The results of this study indicate that: (1) Company size has a significant positive effect on the sustainability report disclosure at PT Bank SMBC Indonesia Tbk, PT Bank Rakyat Indonesia (Persero) Tbk and PT Bank Mandiri (Persero), Tbk; (2) Public ownership has a significant negative effect on the sustainability report disclosure at PT Bank SMBC Indonesia Tbk, PT Bank Rakyat Indonesia (Persero) Tbk and PT Bank Mandiri (Persero), Tbk.